Cold snare polypectomy versus hot snare polypectomy in endoscopic treatment of small polyps - Aslan, Fatih; Camcı, Mehmet; Alper, Emrah; Akpınar, Zehra; Arabul, Mahmut; Çelik, Mustafa; Ünsal, Belkıs (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: The removal of small colon polyps by hot snare polypectomy (HP) is a commonly used method. Polypectomy with a cold snare (CP) has been increasingly utilized in recent years. Each method has its own advantages and disadvantages. Herein, we explored the efficacy and safety of each method. Materials and Methods: Between January 1, 2012 and June 30, 2012, 97 consecutive patients with small colorectal polyps ranging from 5-9 mm in size were separated into either the CP or HP group. Demographic data, the duration of polypectomy, and pathology reports were recorded. Results: Seventy-seven polyps were removed from 49 patients in the CP group, and 71 polyps were removed from 48 patients in the HP group. There was no significant difference between the groups with respect to gender, age distribution, number of polyps, or indications for colonoscopy. The mean polyp size was 7.21±1.4 mm in the CP group and 7.56±1.45 mm in the HP group (p=0.111). There was a significant difference in the mean procedure time between the two groups (CP, 25.71±4.3 sec; HP, 70.28±11.3 sec, p<0.001). One patient (1.3/1.4%) from each group developed post-polypectomy bleeding that required treatment. Histological evaluation revealed that 10 of the polyps (6.75%) were advanced adenomas. Pathological examination showed that the polyps were not completely removed in 4 patients (5.13%) in the CP group and 4 patients (5.63%) in the HP group (p=0.89). Conclusion: CP is an effective and safe method that shortens the polypectomy duration in small polyps (≤9 mm) compared to HP.